Material Exchange in Photoreceptor Transplantation: Updating Our Understanding of Donor/Host Communication and the Future of Cell Engraftment Science - Nickerson, Philip E. B.; Ortin-Martinez, Arturo; Wallace, Valerie A. (Frontiers in Neural Circuits, 2018)
Considerable research effort has been invested into the transplantation of mammalian photoreceptors into healthy and degenerating mouse eyes. Several platforms of rod and cone fluorescent reporting have been central to refining the isolation, purification and transplantation of photoreceptors. The tracking of engrafted cells, including identifying the position, morphology and degree of donor cell integration post-transplant is highly dependent on the use of fluorescent protein reporters. Improvements in imaging and analysis of transplant recipients have revealed that donor cell fluorescent reporters can transfer into host tissue though a process termed material exchange. This recent discovery has chaperoned a new era of interpretation when reviewing the field’s use of dissociated donor cell preparations, and has prompted scientists to re-examine how we use and interpret the information derived from fluorescence-based tracking tools. In this review, we describe the status of our understanding of material exchange in photoreceptor transplantation. In addition, we discuss the impact of this discovery on several aspects of historical rod and cone transplantation data, and provide insight into future standards and approaches to advance the field of cell engraftment.